ESTIMATION OF ABOVE GROUND AND BELOW GROUND CARBON IN PROTECTED PEAT FOREST, SINAR WAJO, MENDAHARA ULU, TANJUNG JABUNG TIMUR, JAMBI - MEILAWATI DEWI - NIM 11514037 , INDRI
Peat forests are one of the most endangered ecosystems in Indonesia due to pressure from human activities, one of which is conversion into oil palm plantations. The aim of this research is to know the carbon deposits at both above and below of both research sites, namely peat forest and peat forest that converted into oil palm plantations. The determination of above ground carbon in protected peat forests, assumed to be limited only from tree with diameter more than 20 cm and the determination of above ground carbon in oil palm plantations, is limited to palm tree biomass (Elaeis guineensis) and Areca catechu. Determination of below ground carbon, assumed to be obtained from soil carbon stores. Inventory of tree diameter, dominant plant diameter and its age, soil sampling were conducted on transect line consisting of 6 plots measuring 20m x 20m in each research site. Peat depths in protected peat forests and oil palm are 6 m and 3.6 m respectively. The results of inventory from the six plots of protected peat forests were 26 individual trees with a diameter range of 20-95 cm from 10 species and on oil palm plantation, obtained 44 individual palm trees and 45 individual of Areca catechu plants. The results of calculation of above ground carbon at both locations respectively of 114.56 tons C/ha and 77.754 tons C/ha. The below ground carbon at both locations were 6,186.155 ton C/ha and 3,908.42 tons C/ha respectively. The amount of above and below carbon at both locations is 6,300.715 tons C/ha and 3,986.18 tons C/ha. Carbon stores lost due to forest conversion amounted to 2,314.53 tons C/ha. This study shows that conversion of peatland protected forests into palm plantations can reduce in carbon savings up to 36.73%.